Śrīsamarthavāgdevatecyā caraṇ̃ī arpilelā pahilā sumanahāra : Śrīsamarthavāgdevatāmandira, udghaṭana nibandhamālā, 1857 Jyeshṭha śuddha 13 (Rāmadāsa āṇi Rāmadāsī ;, 1936)
Festschrift brought out on the inauguration of Śrīsamarthavāgdevatāmandira; comprises contributed articles on the life and works of Rāmadāsa, b. 1608, Hindu religious leader and history of Samartha Sampradaya, a sect founded by him.